Penelusuran Miskonsepsi Operasi Bilangan Bulat dalam Pembelajaran Matematika Pada Mahasiswa PGMI dengan Menggunakan Cri (Certainty of Respon Index) - Ulum Fatmahanik (IAIN Ponorogo, 2018)
Abstract: The academic anxiety in this paper is the misconception of MI prospective teachers at IAIN Ponorogo in understanding the concept of integer operations. This study aims to trace the misconception of integer operations which includes addition, subtraction, multiplication and division by using a number line. The research method used is descriptive qualitative. The subjects of this study are students of GMI.D class of PGMI IAIN Ponorogo who are taking the course of mathematics learning MI which amounted to 32 students. To trace the misconception of students used Certainty of Response Index (CRI) so as to distinguish between students who have misconception with students who do not understand the concept. The instrument used in this study is a test in the form of a diagnostic test in the form of essays accompanied by Certainty of Response Index (CRI), and interviews conducted on students who experience misconception. Based on the results of the search for misconceptions of integer operations the causes of such misconceptions are 1) the principle of using the number lines in inconsistent integer operations; 2) count operation and type of number; 3) the interpretation of the form a + (-b); a - (-b); a x b and a: b, 4) the number of irrelevant reference books; 5) wrong concept of integer operation. ملخص: المشكلة الدافعة لإجراء هذه الدراسة هي المفاهيم الخاطئة لدى طلاب قسم التربية لإعداد مدرسي المدارس الابتدائية الجامعة الإسلامية الحكومية فونوروغو في فهم مفهوم عملية عدد صحيح. هدف هذا البحث إلى العثور على المفاهيم الخاطئة عن عملية عدد صحيح المحتوية على الجمع، والطرح، والتقسيم باستخدام الخط العددي. استخدم هذا البحث طريقة البحث الوصفي الكيفي. وموضوعات البحث هي طلاب الصف GMI.D قسم إعداد معلمي المدارس الإبتدائية الجامعة الإسلامية الحكومية فونوروغو وهم يدرسون تعليم الرياضيات للمدارس الإبتدائية، وعددهم 32 طالبا. وللعثور على المفاهيم الخاطئة لدى الطلاب استخدمت أداة Certainty of Response Index (CRI) حتى يمكن التفريق بين الطلاب المصابون بالمفاهيم الخاطئة والطلاب غير الفاهمين للمفاهيم. وأداة البحث المستخدمة هي الاختبار التشخيصي وفيه الأسئلة الاستيعابية ومعها Certainty of Response Index (CRI)، والمقابلة التي تجرى على الطلاب المصابين بالمفاهيم الخاطئة. ونتائج البحث دلت على أن أسباب وقوع المفاهيم الخاطئة لدى الطلاب هي : 1) أساس استخدام الخط العددي في عملية عدد صحيح الغير المنضبط، 2) عملية الحساب وأنواع العدد، 3) تفسير الشكل a + (-b); a – (-b); a x b dan a : b, ، 4) كثرة المراجع غير المناسبة، 5) المفهوم الخاطئ عن عملية العدد الصحيح.